(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
This paper objectively analyzes the challenges faced by the teaching of engineering mathematical analysis, analyzes the connotation and essence of problem-oriented learning and teaching, puts forward the problem-oriented learning and teaching mode, and tries to improve the teaching quality of engineering mathematical analysis.